TIPOLOGI PERMUKIMAN KUMUH KAWASAN PESISIR DI KELURAHAN WOLOMARANG KOTA MAUMERE (Slum Typology In Coastal Zone of The Wolomarang District Maumere City) - Hamid, Nevi Vilianty; ., Sunarti (Jurnal Pengembangan Kota, 2013)
The higher the population growth is the main factor driving the increase will need space, this is experienced by most of the town of Maumere wake region located in the coastal zone. Since several Â decades ago, many coastal areas visited and occupied by people from other regions one of which is Sulawesi. Bajo society known as the sailors accomplished by bringing habits/ customs of the region of origin, they occupy the coastal areas in the Wolomarang District and start doing activities around the coast such as living with inadequate infrastructure. Most of the people work as fishermen with low incomes who can only meet the needs of life in the form of clothing, food and potluck board. Settlements in the coastal area currently has problems of slum formation as seen from the physical building and environmental conditions that have no drainage and sanitation. Â This study aims to identify the cause of the formation of slums typology of coastal areas in the Wolomarang District Maumere City. To achieve these objectives is necessary to identify the assessment of physical and non physical aspects, social aspects of cultural, economic, regiona characteristics, and policy aspects of coastal spatial planning. Coastal areas has also become one of the central development region of East Nusa Tenggara Province.The method used in this study is to perform quantitative data collection through field surveys (questionnaires, interviews and observations) and a survey instansional (government). Respondents in this study were in the Wolomarang District coastal communities and relevant agencies in the town of Maumere. Data and information from the public and relevant agencies will be directly assessed based on the mapping, frequency distributions and descriptive qualitative analysis.The results of some analysis has been done shows that the typology of coastal slums Wolomarang District is the settlement stage type, the type of semi-permanent and permanent type. Typology of slum formation in the coastal zone is influenced by two factors: economic factors related to location of work and low incomes, and a very strong cultural factors inherent in the society that is accustomed to living close to the sea by building a temporary condition. In its development to date in coastal settlements Wolomarang District the bay waters are carried out by reclamation, and the quality of slum settlements are included in weight. Location of residential communities that are along the road environment and spread irregularly, describe the condition of the settlement were not well ordered. The proposed recommendation is that the government needs to improve supervision and control of construction-related permits in coastal areas and the need for provision of basic infrastructure, i.e. drainage, sanitation and solid waste as well as increasing public knowledge related to the maintenance of settlements.